Assessment of Mandibular Incisive Canal and Anterior Loop in Cone Beam Computed Tomography in Vietnamese Mature Patients: A Retrospective Study - Le, Anh Kha; Tran, Thao Phuong; Nguyen, Tra Thu; Pham, Loc Nguyen Gia; Nguyen, Trung Thanh; Do, Viet Hoang (Journal of Dentistry Indonesia, 2024)
Objective: This study aimed to assess the anatomical length of the mandibular incisive canal and anterior loop and the distance to surrounding structures. Methods: Our study was conducted on 70 cone beam computed tomography (CBCT) films of 70 Vietnamese adult outpatients (40 females, 30 males) at Hanoi Medical University, Vietnam. T-test was applied to assess the difference between the two sides and genders. Results: The mean length of the mandibular incisive canal (MIC) was 12.83 ± 5.13 mm. The anterior loop (AL) prevalence was 62.86%, with an average length of 2.37 ± 0.90 mm. The difference between the right and left sides was statistically significant (p < 0.05), measuring 2.51 ± 0.87 mm and 2.24 ± 0.92 mm, respectively. Our research findings revealed that the distance from the MIC to the alveolar border was approximately twice as long as the distance to the inferior border, with measurements exceeding 17 mm, and it was closer to the buccal cortical bone than the lingual border. Conclusion: The length of AL on the right side was greater. Due to the high prevalence of the MIC and the AL, clinicians should observe the mandibular incisive canal and anterior loop on CBCT scans before performing clinical procedures to avoid injuries.